The Person God Is - Bertocci, Peter A. (Hoboken : Taylor and Francis, 2013)
First published in 2002. Routledge is an imprint of Taylor & Francis, an informa company.
IIIII; IV; V; VI; XIV. Free Will, The Creativity of God, and Order; I; II; III; IV; V; VI; VII; VIII; IX; Part 4: Religion as Co-Creation with God; XV. Three Visions of Perfection and Human Freedom; I. Freedom-Beyond Tension; II. Freedom -- in Fulfilment; III. Freedom -- as Creative Tension; IV. Perfection as Creative Insecurity; XVI. Religion as the Pursuit of Creativity by God and Man; I. Can a Good God Allow Evil?; II. What Makes Human Life Worth While?; We need to be loved; Must love not protect freedom?; Could God be good and not allow creativity?; Is it enough to be loved?
Can love be prudential only?
Description based on print version record.
Keywords: God; Philosophical anthropology; Religion -- Philosophy; God; Philosophical anthropology; Religion -- Philosophy; RELIGION / Agnosticism; Electronic books